Effect of Rice Husk Bioactive Compost Charcoal Application on the Agronomic Characteristics of Peanut (Arachis hypogaea L.) on Alluvial Soil - Agus Suyanto; Urai Suci Yulies Vitri Indrawati; Shinta Rosalina; Edi Kurniadi (The University of Lampung, 2025)
Peanut production on alluvial soil faced challenges due to low soil fertility. The application of soil amendments such as bioactive compost charcoal (BCC) was necessary to improve alluvial soil fertility. The aim of the study was to assess the effect of rice husk BCC application on the agronomic characteristics of peanut in alluvial soil. The research was conducted using a Completely Randomized Design (CRD) and analyzed using the F-test and Tukey's test at 5% significance level. The study design included 4 samples and 6 treatment levels: d1 (20 g/polybag), d2 (40 g/polybag), d3 (60 g/polybag), d4 (80 g/polybag), d5 (100 g/polybag), and d6 (120 g/polybag). The observation variables included plant height, number of branches, number of pods, pod wet weight per plant, and pod dry weight per plant. The data analysis results showed that the application of BCC had a significant effect on the agronomic characteristics of the peanut plants. The application of BCC at a dose of 120 g/polybag showed the best results and was recommended for use on alluvial soil with crop yield of of 31.72 g fresh pod or 24.86 g dry pod weight. Keywords: Agronomic characteristics, Alluvial soil, Bioactive compost charcoal, Peanut, Rice husk.